Poly(3,4-Ethylenedioxythiophene):Poly(Styrene Sulfonate)/Boron Carbide Hybrid Composites with Improved Thermoelectric Performance - Ugraskan, Volkan; Tari, Esra; Yazici, Ozlem (SPRINGER, 2021)
Hybrid composites are promising materials for producing high-performance thermoelectric (TE) materials by combining the superior properties of both components. This study was conducted to investigate the effects of boron carbide (B4C) on the TE performance of poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS). TE studies demonstrated that the addition of B4C enhances the electrical conductivity of pristine PEDOT:PSS from 11.1 S cm(-1) to 1083.8 S cm(-1). Furthermore, the power factor of pristine PEDOT:PSS was enhanced from 0.25 mu W m(-1) K-2 up to 237 mu W m(-1) K-2. The obtained results indicate that B4C is a suitable additive for polymer-based TE composites.
Keywords: Boron carbide; poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate); thermoelectric performance; seebeck coefficient; conductive polymer; BORON-CARBIDE; POWER; PROPERTY; PEDOTPSS; PROGRESS; POWDER; FILM; Engineering; Materials Science; Physics